2018
DOI: 10.4047/jap.2018.10.4.265
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of new implant impression technique using dual arch tray and bite impression coping

Abstract: PURPOSEThe purpose of this in vitro study was to evaluate the accuracy of a new implant impression technique using bite impression coping and a dual arch tray.MATERIALS AND METHODSTwo implant fixtures were placed on maxillary left second premolar and first molar area in dentoform model. The model with two fixtures was used as the reference. The impression was divided into 2 groups, n=10 each. In group 1, heavy/light body silicone impression was made with pick up impression copings and open tray. In group 2, pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Recently, there have been many studies analysing the 3D deviations calculated by superimposing the 3D digital images to evaluate the dimensional accuracy 21,22 . The technique has also been introduced for 3D volumetric analysis to assess the alternation between pre‐ and post‐operative STL models 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been many studies analysing the 3D deviations calculated by superimposing the 3D digital images to evaluate the dimensional accuracy 21,22 . The technique has also been introduced for 3D volumetric analysis to assess the alternation between pre‐ and post‐operative STL models 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…This could indicate a higher reproducibility of results with the open implant impression. The mean deviation of 43.6 µm was an acceptable difference between the master cast and stone cast and was procedurally unavoidable [ 18 , 19 ]. Assuming the same measured variables, our study did not confirm the claim that the nt-VAL-Jig would achieve better accuracy than the open-tray implant level impression.…”
Section: Discussionmentioning
confidence: 99%
“…Polyether and polyvinyl siloxane materials are most frequently used for implant impressions. Both materials show small inaccuracies in the transfer of the implant impression [ 18 , 19 ]. Due to expansion, the master cast can show altered dimensions compared to the oral situation [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 Similar to previous research, this study showed that the distances measured on the original model could not be ideally transferred to the final cast, and that the spatial coordinates of the implants changed relative to each other when transferred to the cast. 10,23,24 The reason might be the movement of the metal copings when opening or closing the guiding rods or attaching the analog, 10,25 the dimensional changes of the gypsum, 26 the shrinkage of the acrylic resin when the copings were connected to each other, 10,25,26 changes in the impression material, 25 the depth of implant placement, 27 soft tissue adhesion (since it could modify the mucosal aspect around the implant), 28 the duration of the use of the dental stone, 29 the implant-abutment interface, 30 machining tolerance (0.6-136 μm), 20 or the operator's error, which is minimally 30 μm in the laboratory setting, but may increase in the oral environment. 31 Moreover, different methodologies can yield variable results.…”
Section: Discussionmentioning
confidence: 99%